CO2 towards fuels: A review of catalytic conversion of carbon dioxide to hydrocarbons. Issue 2 (April 2021) - Garba, Mustapha D.; Usman, Muhammad; Khan, Sikandar; Shehzad, Farrukh; Galadima, Ahmad; Ehsan, Muhammad Fahad; Ghanem, Akram S.; Humayun, Muhammad
Graphical abstract: Zeolite and non-zeolite catalysts for CO2 valorization into hydrocarbon fuels. Highlights: Excessive amount of CO2 emission in the atmosphere causes global warming. Chemical methods for CO2 conversion are highlighted as the best options. Catalysts based on zeolites are currently being explored for hydrocarbons production. Fe-based non-zeolitic catalysts are the most widely used for hydrocarbons production. Zeolitic-imidazole frameworks (ZIFs), covalent-organic frameworks (COFs), and metal-organic frameworks (MOFs) are probably selective catalysts for CO2 conversion to hydrocarbons. Abstract: Meeting the ever-increasing global energy demands is one of the serious challenges of the 21st century. It is estimated that about 80% of the global energy demand is supplied by the fossil fuels which in turn promote global warming upon their consumption and cause harmful effects on the environment. One of the major causes of global warming is the excessive accumulation of CO2 into the atmosphere. An important way for mitigating the excessive amount of CO2 is to transform it into the hydrocarbons (HC) fuels. In this article, we have addressed various issues aroused by CO2 emission and their possible solutions. Various routes for CO2 upgrading into HC fuels are comprehensively elaborated. Furthermore, we have focused on the heterogeneous catalysis for CO2 conversion to value-added HC fuels by utilizing zeolite and non-zeolite based catalysts. The role of noble metals-based catalysts (such as Rh and Ru) and the transition metals containing Ni-species supported on zeolites in CO2 conversion to (HC) fuels is discussed. In addition, the role of Fe- and MOFs based non-zeolite based catalysts for the generation of HC fuels via the CO2 hydrogenation is also discussed. Finally, this review article highlights the prospective areas for research and technology advances. In brief, this review is focused on zeolite and non-zeolite based catalytic route for CO2 to HC fuel and reflects its importance for both the industries and academia.